Web-Based Mail Management Information System at SMA Negeri 1 Sidareja - Sigit Priyoga; Rosihan Ariyuana; Dwi Maryono (Journal of Informatics and Vocational Education, 2023)
Every institution including schools has the responsibility to manage archives, especially letters. But the conventional methods of mail management take up a lot of time and space with the risk of losing documents. With a mail management information system, it can simplify and speed up mail management and minimize the risk of losing documents. This application use Yii2 framework and MySQL for the database. Rapid Application Development used in this research and 5 of 8 aspect ISO 25010 for the evaluation. With good results on all evaluation aspects this application can be used in a school environment.